Opportunities and Challenges of Digital Transformation for Creative Economy Development: Study Literature Review - Wibowo, Nyuherno Aris; Wahyudi, Eko Juni; Ismawati, Lilik; Hermawan, Agus; Wardana, Ludi Wishnu (International Journal of Business, Law, and Education, 2024)
Digital transformation has become a global trend that affects all aspects of human life. In Indonesia, digital transformation can accelerate economic growth, especially in the creative economy sector. One of them is efficiency in the use of technology, investment in digital infrastructure and increasing financial access. The aim of this research is to analyze the opportunities and challenges related to the policy of accelerating digital transformation in the development of the creative economy in Indonesia. The research found that there are various opportunities that can be exploited in developing the creative economy in Indonesia through accelerated digital transformation policies, challenges that must be overcome, such as low technological accessibility and inadequate infrastructure. Research shows that accelerated digital transformation policies can be a driver of creative economic growth in Indonesia which must be adapted to local conditions and accompanied by efforts to increase technological accessibility and adequate infrastructure. This article was prepared based on the results of a literature study to answer the main research questions about transformation. digital and how to implement strategies in various business and government sectors